Shaker mutants lack post-tetanic potentiation at motor end-plates. - Delgado, R.; Latorre, R.; Labarca, P. (European Journal of Neuroscience, 1994)
The two-electrode voltage clamp technique was employed to measure end-plate currents in larval neuromuscular junctions of wild-type (Canton-S) and of three different Drosophila Shaker mutants: ShakerKS133, Shaker102 and f5Shaker5. In the Shaker mutants, nerve-evoked end-plate currents (neepc) were 4-5-fold larger than those measured in Canton-S. Shaker motor end-plates were found to lack post-tetanic potentiation (PTP), but could undergo facilitation. Moreover, PTP but not facilitation was lost in wild-type larvae if the neuromuscular junction was exposed to 4-aminopyridine (4-AP), a blocker of Shaker A-type K+ currents. End-plate currents were depressed by Ca2+ channel blockers like Mg2+, at millimolar concentrations, and Co2+ and Cd2+, at micromolar concentrations, but not by nifedipine (100 nM) and verapamil (100 nM). After exposure to Ca2+ channel blockers, Shaker end-plates exhibited PTP. In particular, Cd2+ was most effective in depressing neepcs and in restoring PTP in all Shaker mutants. The results obtained indicate the abnormal function of Shaker K+ channels at motor nerves specifically abolishes PTP in Drosophila larval neuromuscular junctions.